Modern methods of the style approach to the phenomena of musical creativity and performing (Pedagogy of Higher and Secondary Education, 2009)
In the article basic distinctions of display of style technology’ of creativity in activity of composers and performers are characterized.
Keywords: style approach; piano performing; intonational idea; symbolism